Design of a Smart Baby Monitor for Parents and Caregivers with Hearing Loss - Santamaría-Solís, Ana P. (2024)
Babies demand constant and dedicated attention during their growth process to ensure their well-being and optimal development. Immediate caregiver attention is essential to ensure and safeguard a baby's safety, as well as to meet their physical and emotional needs. Many parents and caregivers may have disabilities such as hearing limitations, which can lead to delays in attending to the needs of the baby under their care. Due to this, many parents and caregivers have sought various solutions, but many of these are limiting; for example, some only work based on the caregiver's condition, such as being awake or alert. Additionally, other alternatives rely on monitors or cameras that require extra attention and can act as distractions from other activities, affecting the productivity and autonomy of parents and caregivers. Using the design thinking method, interviews with deaf parents, and an analysis of products targeted to this market, the proposal was made to develop a notification product that maximizes the senses of sight and touch of the parent or caregiver. This product can be used at any time of the day, in different places, and offers greater privacy and independence to parents.